Severe Multisystem Involvement of Chronic Granulomatous Disease in a Pediatric Patient. (7th May 2018) - Bayramoglu, Zuhal; Adaletli, Ibrahim; Caliskan, Emine; Acar, Manolya; Hancerli Torun, Selda; Somer, Ayper
Abstract: Chronic granulomatous disease (CGD) is a rare primary immunodeficiency disorder identified by recurrent pyogenic and fungal infections infections secondary to defective nicotinamide adenine dinucleotide phosphate oxidase enzyme. In the present study, we demonstrated a case with a history of multiple segmental lung resections because of invasive bronchopulmonary aspergillosis, multifocal hepatic and splenic granulomas, bilateral adnexal calcific foci presumed to be related with old granulomatous infection and finally gastric outlet obstruction secondary to the involvement of the stomach wall thickening with granulomatous tissue. This is an extremely severe case of CGD with multiorgan involvement within a 10-year period after the diagnosis. Gastric antral involvement may mimic inflammatory bowel diseases in such cases, and intestinal involvement can reliably be demonstrated via ultrasonography. Spontaneous resolution of the antral involvement was observed in the follow-up.